PEMBUATAN DAN SOSIALISASI WEBSITE SEKOLAH PADA SMP INDRIASANA - Natalia Regina Devi; Hendrik Fery; Diana Putri Arini; Hadi Alvaro; Stevani Fatrisia Putiastanti (Universitas Sanata Dharma, 2021)
Indriasana Palembang Junior High School is a private school in the center of Palembang city. The school complained about the lack of information and promotion media to students and student guardians. During this time guardians of students need to come to school to get information about student exams, school report, admission of new students and extracurricular activities. Based on the background of the problem, we created a school website at Indriasana Middle School. Our method is conducting interviews with school principals, student representatives and teachers about the obstacles that have been happening all this time. After the website is created, we make a socialization website introduction to the teacher. Based on the results of the school website loading and socialization evaluation, all teachers (n = 14) said they were satisfied with the website. 86% of teachers think that school websites can be used as a means of school promotion, 14% think they can be used as information media.